The association between HLA and non-Hodgkin lymphoma subtypes, among a transplant-indicated population. Issue 12 (15th October 2019) - Zhong, Charlie; Gragert, Loren; Maiers, Martin; Hill, Brian T.; Garcia-Gomez, Jean; Gendzekhadze, Ketevan; Senitzer, David; Song, Joo; Weisenburger, Dennis; Goldstein, Leanne; Wang, Sophia S.
Abstract: Several studies have implicated HLA in non-Hodgkin lymphoma (NHL) subtype etiology. However, NHL patients indicated for stem cell transplants are underrepresented in these reports. We therefore evaluated the association between HLA and NHL subtypes among a transplant-indicated population. One thousand three hundred and sixty-six NHL patients HLA-typed and indicated for transplant at the City of Hope National Medical Center (Duarte, CA) were compared to 10, 271 prospective donors. Odds ratios and 95% confidence intervals were calculated for HLA haplotype and alleles, adjusted for sex and age. The HLA-A*0201∼C*0602∼B*1302∼DRB1*0701∼DQB1*0201 haplotype was significantly associated with follicular lymphoma (FL) risk among Caucasians. Several haplotypes were associated with diffuse large B-cell lymphoma (DLBCL) risk among Caucasians, including the previously implicated DLBCL risk loci, HLA-B*0801 . The HLA-A*0101 allele was also observed to be associated with mantle cell lymphoma (MCL) risk. Our results support the association between previously reported susceptibility loci and FL and suggest potentially new DLBCL and MCL risk loci.